Disturbance observer-based disturbance attenuation control for a class of stochastic systems - Wei, Xin-Jiang; Wu, Zhao-Jing; Karimi, Hamid Reza (Automatica (Oxford), 2016)
This paper studies a class of stochastic systems with multiple disturbances which include the disturbance with partially-known information and the white noise. A disturbance observer is constructed to estimate the disturbance with partially-known information, based on which, a disturbance observer-based disturbance attenuation control (DOBDAC) scheme is proposed by combining pole placement and linear matrix inequality (LMI) methods.